Optimasi Produktivitas Usaha Mikro Kecil dan Menengah di Desa Sidowungu Kecamatan Menganti Kabupaten Gresik Melalui Pelatihan dan Pendampingan Manajemen Produksi, Keuangan dan Pemasaran - Erwan Aristyanto; Agus Sarwo Edi (LPMP Imperium, 2023)
This Community Service Activity is targeted at Small and Medium Enterprises in Sidowungu Village, Menganti District, Gresik Regency. The problems of our MSME partner named Mrs. Nur who produce intestinal chips are dominant in terms of marketing (eg product quality standards, demand for products, lack of product variety, implementation of promotional activities and price competition). In addition, the unstable supply and price of raw materials and other supporting materials (for example: scarcity of raw material supplies and prices of raw materials which tend to fluctuate). The solutions provided for problems in the production sector, the team will provide assistance and training on product quality standards, assistance and training for MSME product development, the use of deep fryers. Assistance and training for MSME product development. Consultation/testing at the UWP Science Laboratory. Counseling on food hygiene from health center cadres. Solutions to problems in the field of Finance, the team will provide training and assistance in making simple bookkeeping to find out the progress of their business and solutions to problems in the field of Marketing, the team will accompany them to make modern and practical labels with the brands they create. Then accompany them to do offline and online marketing so that their market reach is wider. Offline, brochures and banners will be made for these products, while online it will be done by making WhatsApp contacts and marketing through market places. For online marketing, it will be preceded by training and IT assistance involving partners and partner children. Outcome Targets are solutions to the problems they face, presenters in national seminars, scientific publications through national journals, publications in the mass media, intellectual property rights, increasing the quality and quantity of socio-religious behavior, increasing the entrepreneurial spirit, increasing the application of science and technology, and increasing the value of caring each other in the local community. The method used is training and assistance to partners. The plan that will be carried out by the team is to provide assistance and training in the fields of production, finance and marketing. After that the team will escort partners to evaluate each activity program. Then assist partners in sharing knowledge with the wider community. With the implementation of this Community Service activity program, it is hoped that revenue will grow so as to increase the welfare of partners.